Integrating Local Wisdom in the Practice of Farmland Pawn: A Narrative Literature Review Using the Maqasid al-Shariah Approach - Sapinah; Muslimin H. Kara; Rahman Ambo Masse; Abdul Wahid Haddade (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2025)
This study analyzes how farmland pawning has evolved in Indonesian agrarian communities by integrating local wisdom and the evaluative framework of maqāṣid al-sharī‘ah. Adopting a narrative literature review, it brings together findings from Islamic economics, rural anthropology, and legal analyses. The study traces the shift in farmland pawning from a solidarity-based to a more commercialized system. This change raises ethical concerns. These concerns include unequal benefit distribution, ambiguous contractual terms, prolonged pawning, and the potential rise of riba and gharar—contrary to Islamic principles of property protection and justice. The findings show that local wisdom values such as mutual cooperation (gotong royong), communal trust, and deliberation (musyawarah) remain strategically important for harmonizing customary practices with Islamic economic principles. The bay‘ al-wafā’ model emerges as an alternative more aligned with maqāṣid al-sharī‘ah. It clarifies contracts, ensures redemption, and reduces exploitation. This study offers a conceptual framework linking local culture with Islamic law. It provides recommendations for creating a fair, ethical, and sustainable method of farmland pawning in the modern rural economy.